Caracterização geológica do perfil laterítico no município de Rondon do Pará, bloco sul do projeto Alumina Rondon - Baptistella, Bruno [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This completion of course work has as its object of study the Bauxite Province of Paragominas regarded as the richest Amazon bauxite province and whose genesis is related to laterization processes responsible for the formation of mineral deposits of the Rondon Alumina Project, designed to assess areas in the southeast of Pará State, for mineral resources exploration of bauxite, which is the main source of aluminum in the country. Located in the region of Rondon do Pará - PA, the study area is geologically inserted in Lithostratigraphic Unit called Cobertura Laterítica Matura (Mature Lateritic Cover), formed by alteration of paleotropics Cretaceous siliciclastic rocks, and its geomorphology corresponds to a broad plateau with displays of representative profiles of the processes that acted in the region. In this context, the present research aims to characterize the geological evolution of the laterite profile, with detailed studies in the area, geological description of the formations from the bauxite surfaces, and mineralogical composition litochemical of different horizons that were correlated and deployed in an evolutionary model compatible with its traits. The data collected during the analysis subsidized metalogenetic understanding of the processes that acted in the enrichment of aluminum and iron as well as the redistribution of the latter modified profile. The results and information were embodied in the form of geological characterization of the different constituents of mineral associations of bauxite horizons, similarities or differences in both textural and structural aspects, in order to propose a evolutionary model with retaken of gibbsitization processes

Este trabalho de conclusão de curso tem como objeto de estudo a Província Bauxitífera de Paragominas considerada a mais rica da província bauxitífera amazônica e cuja gênese está relacionada a processos de laterização, responsáveis pela formação dos depósitos minerais como o estudado pelo Projeto Alumina Rondon, objetivando avaliar áreas com interesse mineral na região sudeste do Estado do Pará, para exploração de bauxita. Localizada nas proximidades da cidade de Rondon do Pará – PA, a área estudada está inserida geologicamente na Unidade Litoestratigráfica denominada Cobertura Laterítica Matura, formada por alteração paleotropical de rochas siliciclásticas do Cretáceo, e sua geomorfologia corresponde a um amplo platô com exposições de perfis representativos dos processos que atuaram na região. Nesse contexto, o presente trabalho buscou contribuir com o entendimento da evolução geológica do perfil laterítico, com estudos pormenorizados abrangendo desde descrição geológica das formações superficiais bauxitizadas, composição litoquímica e mineralógica dos diferentes horizontes presentes que foram correlacionados e desdobrados em um modelo evolutivo compatível com as características analisadas. Os dados levantados durante as análises subsidiaram o entendimento dos processos metalogenéticos que atuaram no enriquecimento do alumínio e ferro além da redistribuição deste último no perfil de alteração. Os resultados e informações foram consubstanciados na forma de caracterização geológica das diferentes associações minerais constituintes dos horizontes bauxíticos, em suas semelhanças ou diferenças texturais e estruturais, para proposição de um modelo evolutivo com retomada do processo de gibbsitização
Keywords: Projeto Alumina Rondon; Geologia; Bauxita; Determinação mineralogica; Latossolos; Geoquimica; Rondon do Pará (PA)